Reversible size of shear-induced multi-lamellar vesicles - Medronho, B. (2015)
We have investigated the reversibility in the shear-induced multi-lamellar vesicle (MLV) size during stepwise cycling of the shear rate by employing common rheometry, polarized light microscopy and rheo-optic techniques. We thus address the question whether there is a true MLV steady state, irrespective of history. The system studied, was the nonionic surfactant triethylene glycol decyl ether (C(10)E(3)) with a concentration of 40 wt.% in D(2)O and a constant temperature of 25 degrees C. It was found that the MLV size varies reversibly with varying shear rate, and hence there exists a true steady state in the presence of shear flow. The experimental observations of reversibility are however restricted to higher shear rates. Because the transformation of the size results from the shear strain, the process is very slow at lower shear rates, where the steady state cannot be reached within a reasonable experimental time.